Microcosm - Duffy, Maureen (Virago, 1989)
À la House of Shades, Matt, un philosophe de bar, tente de donner un sens aux vies disparates qui se croisent ici : de Judy qui réserve elle-même et ses plus beaux atouts pour un amant du samedi soir, de Steve le professeur de gym qui redoute une chance. rencontre avec une élève dans cet environnement crépusculaire, et avec Matt elle-même, qui a besoin de ces échanges indirects malgré la sécurité de sa relation avec Rae et son sentiment que ce sanctuaire lesbien est aussi une prison, renforçant la culpabilité et l'éloignement des rues de la ville au-delà. Ailleurs, il y a des femmes comme Marie, prisonnière d'un mariage non désiré et incapable d'admettre sa sexualité, et Cathy, pour qui découvrir qu'elle n'est pas « la seule au monde » est une affirmation de son existence. Avec sa structure et son style innovants, reflétant parfaitement les voix et les expériences des femmes contraintes par la société à vivre en marge, The Microcosm reste aussi puissant aujourd'hui que lors de sa première publication en 1966.
Première édition: 1966
Keywords: 1900-1999; 1960-1969; approches et analyses; hétérosexisme; identités LGBTQIA2+; patriarcat; personnes lesbiennes; périodes historiques; roman; sexualité; systèmes d'oppressions; thématiques; travail; violences

Pornography and civil rights: a new day for women's equality - Dworkin, Andrea; MacKinnon, Catharine A. (Organizing Against Pornography, 1988)
"Pornography is central in creating and maintaining the civil inequality of the sexes. Pornography is a systematic practice of exploitation and subordination based on sex which differentially harms women. . . ." With those bold words began the groundbreaking local antipornography law drafted by writer Andrea Dworkin and lawyer Catharine A. MacKinnon. Their completely new legal approach–in which pornography is defined as sex discrimination and therefore a violation of civil rights–would allow anyone injured by pornography to fight back by filing a civil lawsuit against pornographers. First passed in December 1983 in Minneapolis, where it was supported by a grassroots coalition of women, people of color, neighborhood groups, and the city's welfare poor and working poor, this law has transformed the way people of conscience understand the devastating impact of pornography on women's right to equality. This new law also offers hope: an effective legal tool for making sex equality real. In this comprehensive and easy-to-read guidebook, now available on line, the coauthors of the anti-pornography civil-rights ordinance explain: How pornography hurts women and how and why the civil-rights ordinance would make a difference. Why the pornography is so important to women's equality. The truth about the antipornography civil-rights ordinance–what it is, what it does, what it means, how it works. Answers to the lies about it–lies that the media have spread to protect the pornography industry. What you can do to stop the pornographers and further women's equality. "The Ordinance does not take 'rights' away from anyone, . . . it takes the power to hurt women away from pornographers." –from Pornography and Civil Rights
Section: 142 pages ; 22 cm
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; droit; droits des femmes*; féminisme anti-porn; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique et droit; sex1911; sexualité; sofia; thématiques; violences; états-unis

Jeunes femmes et « contre-culture » au Québec - Lamont, Ève (Les Cahiers du Grif, 1986)
https://www.persee.fr/doc/grif_0770-6081_1986_num_34_1_1698
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Pleasure and danger: Exploring female sexuality - Vance, Carole S. (Routledge & Kegan Paul, 1984)
Articles presentés à la Scholar and the Feminist IX conference, tenue le 24 avril 1982 au Barnard College dans la ville de New York.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; plaisir féminin; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sex1183; sexualité; sexualité des femmes*; thématiques; violences; états-unis

Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality - Vance, Carole S. (Pleasure and danger: exploring female sexuality, 1984)
Articles presentés à la Scholar and the Feminist IX conference, tenue le 24 avril 1982 au Barnard College dans la ville de New York.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; plaisir féminin; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sex1183; sexualité; sexualité des femmes*; thématiques; violences; états-unis